(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2024)
After the achievement of the statute of citizenship in the European Union, after the Treaty of Maastricht, the configuration, in the legal system of the EU, of a right to a free movement with autonomous nature, i.e. without connection with the activity and economic foundations that characterized it at the beginning of the community integration process, and that consolidated two freedoms or fundamental rights such as the free movement and freedom of residence in the territory of the Member States of the European Union. These freedoms, enshrined in the Treaties and in the Charter of Fundamental Rights of the European Union, also had an important legislative development and jurisprudential attention; all this at the same time of the consolidation of the Schengen Area with the aim of eliminating border controls. In this work I make an approach to the foundations and configuration of these freedoms, and their consolidation, with particular attention to the scope of personal application and the content of the fundamental freedoms, in addition to the analysis of the most relevant European Court of Justice’s case law in this field to give response to the questions that arise currently in the exercise of these freedoms.